Learn Kubernetes security : securely orchestrate, scale, and manage your microservices in Kubernetes deployments - Huang, Kaizhe; Jumde, Pranjal (Packt Publishing, 2020)
Kubernetes is a widely used opensource orchestration platform for managing container applications. Developers are not yet aware of the pitfalls of a containerized environment. This book takes you through core security principles, best practices, and real-world use cases to learn mitigation or prevention strategies from known attacks and CVEs.